MODEL PENGAJARAN TERBALIK DALAM MATA KULIAH CHUKYU DOKKAI - Amira Agustin Kocimaheni (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
Chukyu  Dokkai  lecture  is  an  intermediate  reading  lecture  which  the  students program  after  taking  the  Shokyu Dokkai,  an  elementary  reading  lecture.  In  the elementary  level of  reading a  lecturer still  takes a very great role  in  the  teaching and learning process. The roles includes guiding and teaching the students to read starting  from  words,  sentences,  paragraph  and  even  the  lecturer  still  use  the translation method. But not for the intermediate level of reading, the methods and techniques of the teaching is more various. One of the models which can be used is  reciprocal  teaching.  This model  puts  the  teacher  or  lecturer  as  a model  and facilitator than a presenter of  the  teaching and  learning process. The students are taught  four  strategies  of  specific  self-understanding  and  control,  namely summarizing,  questioning,  clarifying,  and  predicting.  While  the  teaching  and learning  process  is  taking  place,  the  students  are  actively  involved  in  the discussion  in  their groups. The  lecturer acts as mediator, model, and  trainer. The teaching  and  learning  process will  not  be  a  one way  process where  the  lecturer controls  the  process,  but  the  students  will  also  have  the  chance  to  give  their opinions.  Therefore  it  is  hoped  that  the  students  will  grow  the  responsibility within  them and  the lecturer will stay with  them  to help  them monitor, think and choose the strategy that can be used in the process of studying